DAMPAK OBJEK WISATA SUNGAI HIJAU TERHADAP PEREKONOMIAN MASYARAKAT DI DESA SALO KECAMATAN SALO KABUPATEN KAMPAR - ", Nurfitriani; Sidiq, Siti Sofro (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
This study aims to determine the impact Attractions Green River Community on the Economy In the village Salo Salo District of Kampar.In the method of this study authors used a qualitative research method with descriptive analysis.Based on the research that has been conducted, the results in the can is that the economy of rural communities precisely in the Kampar district salo attraction green river getting quite favorable economic development for the surrounding communities are located area tourist attractionKeywords : Economic Impact, Salo village, Kampar, Green River Tourist Object